Research on Adaptation of Service-based Business Processes - Zongmin Shang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper proposes an adaptation mechanism based on adaptation planning graph for service-based business processes. First, a three-layer representation model of service-based business process is introduced. Second, control-flow patterns of tasks, goal, logic model of service-based business process and adaptation planning graph are introduced to enforce reliability of composite web services at run-time. Finally, a simulation example of adaptation in service-based business processes is given. Simulations prove that this approach can efficiently guarantee the reliability of composite services at run-time. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.4148